The effect of alcohol and placebo on post-error adjustments - Bombeke, Klaas; Schouppe, Nathalie; Duthoo, Wout; Notebaert, Wim (Frontiers in Human Neuroscience, 2013)
Several studies have shown detrimental effects of alcohol on post-error adjustments. In contrast to previous studies, which focused on only one aspect of post-error adaptive behavior, we compared the effect of alcohol and placebo on post-error slowing, post-error reduction of interference and post-error improvement of accuracy. Moreover, we used a between-subjects design (N = 45) comparing a control condition to both an alcohol and an alcohol-placebo condition as to disentangle physiological and expectancy effects of alcohol. In a standard Stroop congruency task, we found that intoxicated participants as well as participants with the incorrect belief of being intoxicated showed significant decreased post-error slowing compared to a control group. Furthermore, we found evidence for a condition-independent post-error increase of interference and post-error decrease of accuracy. The underlying mechanisms of the post-error adaptation effects are discussed in terms of the orienting account (Notebaert et al., 2009).